Pengaruh Penerapan Undang-Undang Otonomi Daerah Terhadap Pelaksanaan Hubungan Internasional Di Yogyakarta - Nyong, Arsil; Lule, Alwadud (Jurnal Ilmiah Wahana Pendidikan, 2025)
With the enactment of the regional autonomy low from the central governmet‟s policy dimention to regions, this is characterized by a centralized to decentralized policy. The shifted it has shifted the paradigm of international relations so that local governments are also part of international relations actors. Yogyakarta is an area that is active in doing overseas cooperation in the form of sister province. Knowing the effect of the implementation of the regional autonomy law on the role of diplomacy in the context of international cooperation in the special area of yokyakarta is important so that it can provide a comprehensive picture of the contribution of the regional autonomy law to the foreign cooperation conducted by the province of Yogyakarta special region. In order to be knowledgeable about the contribution of the regional autonomy law to the role of diplomasi, and it can be the basis of the analysis on the overseas cooperation that has been done. So that this analysis, can be used as a reference in cooperation made and can add khasana of science in the study of international relations. The method used to determine the above problems, using literature research using descriptive-qualitative approach. From research conducted that the law of regional autonomy has changed the local government into actors in the process of cooperation abroad, in several authorities namely education, culture, economy, tourism, infrastructure, environment, technology and labour. Although the laws of regional autonomy have authorized regional governments to engage in foreign cooperation, the regional need clear regulation on the role of paradiplomasi so they can freely exercise their diplomatic roles way juridically determined areas without bypassing the authority of the central government in terms of international cooperation.